Analyzing Writing of Producing Ideas and Using Mechanics through Showing Short Videos - Lihawa, Kartin (Transbahasa, 2023)
This study addresses the challenges students face in writing, particularly in balancing writing theories with idea generation. It focuses on enhancing students' ability to produce clear and logical scientific writing by improving their mechanics application. Despite challenges faced by students in the English Department of FSB UNG, such as difficulty in writing long paragraphs and applying mechanics, the study aims to overcome these obstacles. The research, conducted through eight sessions of